The Influence of Culture on Personality: A Literature Review - Sri Rahayu Wardani; Firman Firman; Riska Ahmad (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
Personality is formed from three factors, namely heredity, environment, and self-image. The environment has a big influence on a person's personality and it is reflected in the behavior shown by the individual himself. Individuals who are raised in a certain society will be shaped by the cultural experiences they receive. A person's personality is obtained starting from the time he is born, starting at that stage a person begins to recognize and know the patterns of behavior that prevail in his community. Thus, the relationship between culture and personality is very close, because humans as a medium for culture and culture influence human behavior.